Regulation and Functional Expression of Cinnamate 4-Hydroxylase from Parsley - Koopmann, Edda (American Society of Plant Physiologists, 1999)
A previously isolated parsley (Petroselinum crispum) cDNA with high sequence similarity to cinnamate 4-hydroxylase (C4H) cDNAs from several plant sources was expressed in yeast (Saccharomyces cerevisiae) containing a plant NADPH:cytochrome P450 oxidoreductase and verified as encoding a functional C4H (CYP73A10). Low genomic complexity and the occurrence of a single type of cDNA suggest the existence of only one C4H gene in parsley. The encoded mRNA and protein, in contrast to those of a functionally related NADPH:cytochrome P450 oxidoreductase, were strictly coregulated with phenylalanine ammonia-lyase mRNA and protein, respectively, as demonstrated by coinduction under various conditions and colocalization in situ in cross-sections from several different parsley tissues. These results support the hypothesis that the genes encoding the core reactions of phenylpropanoid metabolism form a tight regulatory unit.